PENGABDIAN MASYARAKAT TENTANG PEMBEKALAN MANAJEMEN ORGANISASI DALAM KEGIATAN PELANTIKAN DAN ORIENTASI PENGENALAN ORGANISASI DENGAN THEMA BERORGANIASASI DENGAN HATI BERKARYA DENGAN AKSI: Community Service On Provision Of Organizational Management Introduction Activities And Organizational Introduction Orientation With The Theme Organizing With Heart, Working With Action - Yamin, Bahri; Rachman, M. Taufik (Al-Amal: Jurnal Pengabdian Masyarakat, 2025)
The NTT Student Community Organization in Mataram is formed based on regency, sub-district, and religious origin. These organizations include the Manggarai Mataram Muslim Family Communication Forum (FK2M), the Komodo Boleng Mataram Student and Pupil Association (IMPKBM), and several others. Each organization holds annual routines such as the inauguration of new management and an Organizational Introduction Orientation (OSPOR) for new students who are members of the IMPKBM. The methods used are discussions and lectures. The results are organizational management training at the inauguration and orientation events, with the theme "Organizing with Heart, Working0 with Action," a strategic effort to produce administrators and members who possess competence, integrity, and are ready to carry out their duties professionally. Through a series of materials, discussions, simulations, and guidance, participants gained a comprehensive understanding of organizational governance, leadership, communication, and work program planning. These activities not only strengthened technical skills but also instilled the values ​​of empathy, responsibility, and cooperation as the foundation for organizing with a heart-based approach. With this knowledge, it is hoped that administrators will be able to produce tangible results and play an active role in the organization's sustainable development. The origins of IMPKBM are a forum for maintaining unity, fostering brotherhood, and contributing to the development of their home regions.